FGF23 Beyond the Kidney: A New Bone Mass Regulator in the General Population - Bilha, Stefana Catalina; Bilha, Andrei; Ungureanu, Maria-Christina; Matei, Anca; Florescu, Alexandru; Preda, Cristina; Covic, Adrian; Branisteanu, Dumitru (Hormone and Metabolic Research, 2020)
Clinical studies investigating the relationship between fibroblast growth factor 23 (FGF23) and bone mass are controversial, especially in the healthy renal population. Our study is one of the forefronts investigating the relationship between FGF23 and bone mass parameters in the general population, according to age, sex, menopausal, and nutritional status. Cross-sectional study enrolling 123 volunteers between 20–80 years of age without primary osteoporosis under treatment nor secondary osteoporosis, where bone mass (bone mineral density-BMD, bone mineral content-BMC; assessed by Dual X-Ray Absorptiometry-DXA), body composition (DXA evaluation), and also the serum levels of FGF23, parathormone (PTH), 25(OH)D, bone resorption marker C-terminal telopeptide of type I collagen (CTx) and leptin were determined. FGF23 was negatively and independently associated with BMD and/or BMC in all groups. FGF23 contributed to up to 10% (p <0.05) of femoral neck BMD variance in postmenopausal women, but was not an accurate discriminator of normal versus low bone mass (AUC=0.622±0.076). FGF23 did not correlate with 25(OH)D, CTx, body weight, body composition parameters or leptin. FGF23 was independently associated with PTH in premenopausal women and men only. FGF23 was negatively associated with bone mass parameters in both sexes, but was not a fine discriminator between normal bone mass and osteopenia/osteoporosis. The mechanism through which FGF23 acts upon the bone seems independent of the nutritional status, requiring further investigation.
Keywords: FGF23; bone / calcium homeostasis; osteoporosis, osteopenia